2016
DOI: 10.21649/akemu.v22i2.1296
|View full text |Cite
|
Sign up to set email alerts
|

Role of Colour Doppler in Evaluation of Hemodynamic Changes in Chronic Hepatitis C Infection

Abstract: Purpose of the Study: The estimation of the degree of hepatic fibrosis is important for diagnostic and therapeutic management of patients with chronic liver disease, in particular those associated with hepatic viral infections. In cirrhosis portal blood inflow, hepatic resistance and portal venous pressure increase. Doppler sonography is non-invasive diagnostic modality based on hemodynamic parameters. Hemodynamic changes might have developed even in cases with normal findings on B mode sonography. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…1b, 3, and 4). We had found that PVV did not significantly correlate with MELD score; this was concordant with many works of literature [16][17][18][19] who had documented the same issue; however, this was contradicting the Berzigotti et al study, where they reported a low flow velocity of < 20 cm/s in addition to a caliber increase in the main portal vein (MPV) were considered diagnostic features of portal hypertension [20]. However, we did not measure the portal vein diameter, and the possible reason for the contradicting data in the PVV was the heterogeneity of the cirrhotic patients included in various studies, also the type of hemodynamic disturbances, for example, the presence of hyperkinetic syndrome or portosystemic collaterals.…”
Section: Discussionsupporting
confidence: 92%
“…1b, 3, and 4). We had found that PVV did not significantly correlate with MELD score; this was concordant with many works of literature [16][17][18][19] who had documented the same issue; however, this was contradicting the Berzigotti et al study, where they reported a low flow velocity of < 20 cm/s in addition to a caliber increase in the main portal vein (MPV) were considered diagnostic features of portal hypertension [20]. However, we did not measure the portal vein diameter, and the possible reason for the contradicting data in the PVV was the heterogeneity of the cirrhotic patients included in various studies, also the type of hemodynamic disturbances, for example, the presence of hyperkinetic syndrome or portosystemic collaterals.…”
Section: Discussionsupporting
confidence: 92%